Self-Compassion Profile in Lampung Culture Perspective - Adiputra, Sofwan (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2018)
The aim of this research is to conduct a descriptive study about self-compassion profile of Lampung students based onupon the sequence of tribe and sex in STKIP Muhammadiyah Pringsewu Lampung. This research describes the difference of self-compassion level of students based on the tribe in Lampung, and the level of self-compassion based on gender. Self-compassion is the ability to be compassionate to yourself, entertain themselves and care when self-suffering, failures and imperfections. The results from this study explain that women have a lower level of self-compassion than men. In addition, the cultural factors in the students in Lampung do not have a big impact on self-compassion. This is because the people of Lampung who have open characteristics to mingle with other tribes. Self-compassion is expected to become a multicultural competency of a counselor because someone who has a high self-compassion will have the ability to care about the difficulties of others.